(untitled) (Journal of the College of Basic Education, 2022)
The aim of the research is to find out the effect of a training program for applied students on their teaching performance and their social intelligence. The research sample reached (73) students from the fourth stage in the Mathematics Department, the morning study. They were randomly distributed into two experimental groups consisting of (37) male and female students and the control group consisting of (36). Male and female students, and to achieve the objectives of the research, a training program was prepared in which a group of activities and exercises were employed, some of them individual and others group, during the implementation of the training sessions, and the preparation of a note card for teaching performance and a measure of social intelligence, and using the t-test as a statistical method. The results showed that there was a statistically significant difference between the research groups and in favor of the experimental group in both dependent variables.